2021
DOI: 10.3348/kjr.2020.1468
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of a Deep Learning-Based Hybrid (Greulich-Pyle and Modified Tanner-Whitehouse) Method for Bone Age Assessment

Abstract: Objective To evaluate the accuracy and clinical efficacy of a hybrid Greulich-Pyle (GP) and modified Tanner-Whitehouse (TW) artificial intelligence (AI) model for bone age assessment. Materials and Methods A deep learning-based model was trained on an open dataset of multiple ethnicities. A total of 102 hand radiographs (51 male and 51 female; mean age ± standard deviation = 10.95 ± 2.37 years) from a single institution were selected for external validation. Three human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Recently, Lee et al. ( 43 ) suggested a hybrid GP- and TW-based DL system. Two public datasets were used to train a CNN model: (1) 14,236 radiographs from RSNA ( 54 ) and (2) 1,375 radiographs from Digital ( 57 ).…”
Section: Application Of Deep Learning In Endocrinologymentioning
confidence: 99%
“…Recently, Lee et al. ( 43 ) suggested a hybrid GP- and TW-based DL system. Two public datasets were used to train a CNN model: (1) 14,236 radiographs from RSNA ( 54 ) and (2) 1,375 radiographs from Digital ( 57 ).…”
Section: Application Of Deep Learning In Endocrinologymentioning
confidence: 99%
“…Then, it is realized by recognizing the maturity of the bones through the changes of radiographic appearance. There exist two most typical methods for BAA, namely the Greulich-Pyle (GP) method and the Tanner-Whitehouse (TW) method (Lee et al, 2021;Shah et al, 2021). The former one is based on the hand atlas, and its reference dataset consists of a series of left-hand X-ray images derived from the middle socioeconomic class of Caucasian children from the Midwest region of the US from 1931 to 1942.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of deep learning algorithms and the rapid improvement of computer hardware in the past few years, artificial intelligence AI-assisted diagnosis software has begun to be applied in hospitals, among which bone age AI-assisted software is one of the earliest [7][8][9][10][11][12]. AI-assisted diagnosis software for bone age has achieved good diagnostic performance [12][13][14][15][16][17]. Some studies have proven that the results of AI-assisted diagnosis software for bone age are as accurate as those of experts [13,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…AI-assisted diagnosis software for bone age has achieved good diagnostic performance [12][13][14][15][16][17]. Some studies have proven that the results of AI-assisted diagnosis software for bone age are as accurate as those of experts [13,15,18]. While some shown that AI assistance improves the diagnostic accuracy rate of radiologists [12,15,17,19].…”
Section: Introductionmentioning
confidence: 99%